2021
DOI: 10.3389/fcvm.2021.727727
|View full text |Cite
|
Sign up to set email alerts
|

Incident Heart Failure in Patients With Coronary Artery Disease Undergoing Percutaneous Coronary Intervention

Abstract: Background: The contemporary incidence of heart failure (HF) in patients with coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI) remains unclear. This prospective cohort study was designed to study the incidence and predictors of new-onset HF in CAD patients after PCI (ChiCTR1900023033).Methods: From January 2014 to December 2018, 3,910 CAD patients without HF history undergoing PCI were prospectively enrolled. Demographics, medical history, cardiovascular risk factors, cardiac p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In recent years, studies have shown that monocyte chemotactic Protein-1 (McP-1), as a kind of factor mediating the formation of foam cells in monocytes, also plays a role in the inflammatory response of atherosclerosis [ 6 ]. B-type natriuretic peptide, as one of the related hormones secreted by cardiomyocytes, also plays an important role in predicting adverse cardiovascular events [ 7 ]. In addition, as a blood lipid index, Lipoprotein A (LPa) may also play a certain role in the development of coronary heart disease [ 8 ], but there are relatively few studies on the above indexes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have shown that monocyte chemotactic Protein-1 (McP-1), as a kind of factor mediating the formation of foam cells in monocytes, also plays a role in the inflammatory response of atherosclerosis [ 6 ]. B-type natriuretic peptide, as one of the related hormones secreted by cardiomyocytes, also plays an important role in predicting adverse cardiovascular events [ 7 ]. In addition, as a blood lipid index, Lipoprotein A (LPa) may also play a certain role in the development of coronary heart disease [ 8 ], but there are relatively few studies on the above indexes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the CKD group was less likely to receive ACEI/ARB. Previous studies have also shown that ACEI/ARB therapy was accompanied with reduced risks of incident HF (2,22). Moreover, there are some pathophysiologic mechanisms to account for the adverse effect of CKD on incident HFrEF.…”
Section: Discussionmentioning
confidence: 96%
“…Coronary artery disease (CAD) is the most common cause of heart failure (HF) (1). Even after percutaneous coronary intervention (PCI), patients with CAD still have a high risk of incident heart failure with reduced ejection fraction (HFrEF) (2). Thus, it is necessary to identify risk factors and improve prognosis among patients with CAD undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…BNP is synthesized in the heart ventricles, and increase during ventricular dysfunction. Higher BNP was an independent risk factor of new-onset HF [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%